Transcriptomics reveals substance biosynthesis and transport on membranes of Listeria monocytogenes affected by antimicrobial lipopeptide brevilaterin B - Yangliu Liu; Yawei Ning; Zhou Chen; Panpan Han; Tongxin Zhi; Siting Li; Aijin Ma; Yingmin Jia (Food Science and Human Wellness)
Listeria monocytogenes is a worrisome food-borne pathogen threatening global food safety. Our previous study proved that lipopeptide brevilaterin B showed efficient antibacterial activity against L. monocytogenes by interacting with the cell membrane. This research further explored the antibacterial mechanism of brevilaterin B against L. monocytogenes at the sub-minimum inhibition concentration via transcriptomic analysis. Brevilaterin B induced growth inhibition rather than direct membrane lysis in L. monocytogenes at the minimum inhibitory concentration. Transcriptomic analysis showed 1779 difference expressed genes, including 895 up-regulated and 884 down-regulated genes. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes analysis indicated that brevilaterin B influenced multiple pathways of L. monocytogenes, including peptidoglycan biosynthesis, membrane transport (ATP-binding cassette transports, ion transport), cellular metabolism (amino acid and lipid metabolism), ATP synthesis, and activation of the stress response (quorum sensing and bacterial chemotaxis). In conclusion, brevilaterin B affects gene expression related to biosynthesis, transport and stress response pathways on the membrane of L. monocytogenes. The present work provides the first transcriptomic assessment of the antibacterial mechanism of lipopeptide brevilaterin B at the gene level.